Use of High Quantification Evidence in Fair Value Audits: Do Auditors Stay in their Comfort Zone? - Joe, Jennifer R.; Vandervelde, Scott D.; Wu, Yi-Jing (The Accounting Review, 2017)
ABSTRACT Research documents significant management bias and opportunism around the discretionary inputs of audited complex estimates, including fair value measurements (FVMs), which raises questions about auditors' ability to test these estimates. We examine how the degree of quantification in client evidence and client control environment risk influence auditors' planned substantive testing of management's discretionary inputs to FVMs. We find that auditors allocate a lower proportion of effort to testing the subjective inputs to the fair value estimate when the degree of quantification in the client evidence and level of client risk are both high. Further, this tendency persists even after auditors receive a regulatory practice alert reminding them to focus more audit effort on testing fair value (FV) inputs that are susceptible to management bias, and despite the auditors increasing their overall audit effort. Qualitative analyses of the procedures auditors selected indicate that inapt attention to the degree of quantification in evidence is a potential root cause of the difficulty auditors encounter when testing complex estimates. Our results imply that in situations where both quantified and non-quantified data are important to the audit, there is the potential for management to manipulate the evidence they provide to auditors to distract auditors from testing the discretionary inputs to complex estimates that are susceptible to management opportunism. Data Availability: Contact authors for data availability.